Yersinia enterocolitica in sheep - a high frequency of biotype 1A - Söderqvist, Karin (BioMed Central, 2012)
BACKGROUND: Pigs are regarded as the main reservoir for human pathogenic Yersinia enterocolitica, which is dominated by bioserotype 4/O:3. Other animals, including sheep, have occasionally been reported as carriers of pathogenic strains of Y. enterocolitica. To our knowledge, this is the first study performed in the Nordic countries in which the presence of Y. enterocolitica in sheep is investigated. METHODS: Tonsils and faecal samples collected from sheep slaughtered on the island Gotland (Sweden) from September 2010 through January 2011 were analysed for presence of Y. enterocolitica. In an attempt to maximize recovery, several cultural strategies were applied. Various non-selective media were used and different temperatures and durations of the enrichment were applied before subculturing on Cefsulodin Irgasan Novobiocin (CIN) agar. Presumptive Y. enterocolitica colonies were subjected to urease, API 20E and agglutination test. Yersinia enterocolitica isolates were biotyped, serotyped, and tested for pathogenicity using a TaqMan PCR directed towards the ail-gene that is associated with human pathogenic strains of Y. enterocolitica. RESULTS: The samples collected from 99 sheep yielded 567 presumptive Y. enterocolitica colonies. Eighty urease positive isolates, from 35 sheep, were identified as Y. enterocolitica by API 20E. Thirty-four of 35 further subtyped Y. enterocolitica isolates, all from faecal samples, belonged to biotype 1A serotype O:5, O:6. O:13,7 and O:10. One strain was Yersinia mollaretii serotype O:62. No human pathogenic strains of Y. enterocolitica were found in the investigated sheep. Other species identified were Y. kristensenii (n = 4), Y. frederiksenii/intermedia (n = 3), Providencia rettgeri (n = 2), Serratia marcescens (n = 1) and Raoultella ornithinolytica (n = 1). CONCLUSIONS: This study does not support the hypothesis that sheep play an important role in transmission of the known human pathogenic Y. enterocolitica in the studied geographical region. However, because there are studies indicating that some strains of Y. enterocolitica biotype 1A may cause disease in humans, the relative importance of sheep as carriers of human pathogenic strains of Y. enterocolitica remains unclear. Tonsils do not appear to be favourable sites for Y. enterocolitica biotype 1A in sheep.